2002
DOI: 10.1074/jbc.m110535200
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Sequences Targeting Tissue-specific Gene Expression of Hypothalamic and Ovarian Gonadotropin-releasing Hormone in Vivo

Abstract: Molecular mechanisms directing tissue-specific expression of gonadotropin-releasing hormone (GnRH) are difficult to study due to the paucity and scattered distribution of GnRH neurons. To identify regions of the mouse GnRH (mGnRH) promoter that are critical for appropriate tissue-specific gene expression, we generated transgenic mice with fragments (؊3446/؉23 bp, ؊2078/؉23 bp, and ؊1005/؉28 bp) of mGnRH promoter fused to the luciferase reporter gene. The pattern of mGnRH promoter activity was assessed by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…It is of interest to clarify the relationship between annexin A5 expression and gonadotrope-induced apoptosis during the afternoon of proestrus [31]. On the other hand, GnRH may exert chronic effect in peripheral tissues since GnRH and its receptor are expressed in a wide variety of extra-pituitary tissues [32][33][34]. In fact, we recently showed that the expression of annexin A5 in the corpus luteum and also Leydig cells is stimulated by local GnRH [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to clarify the relationship between annexin A5 expression and gonadotrope-induced apoptosis during the afternoon of proestrus [31]. On the other hand, GnRH may exert chronic effect in peripheral tissues since GnRH and its receptor are expressed in a wide variety of extra-pituitary tissues [32][33][34]. In fact, we recently showed that the expression of annexin A5 in the corpus luteum and also Leydig cells is stimulated by local GnRH [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The remainder of the second exon, the third exon and most of the fourth exon code for the GnRH associated peptide (GAP) (Adelman et al 1986, Dong et al 1996, Mason et al 1986) a cleavage product of unknown function that is produced during the processing of the GnRH prohormone. The promoters of the human, rat and mouse GnRH genes have been characterized and regions important for cell-specific expression and regulation of the gene have been identified (Kim et al 2002, Wolfe et al 2002, Wolfe et al 1995, Skynner et al 1999, Pape et al 1999, Lawson et al 1998, Whyte et al 1995, Novaira et al 2012, Novaira et al 2011). The cell-specific regions of the human (Radovick et al 1991) and rat (Mellon et al 1990) GnRH promoters have been used to target large T antigen expression to GnRH neurons in transgenic mice that have been used to develop cell line models.…”
Section: Summary Of Hpg Axismentioning
confidence: 99%
“…However, data from in vivo promoter mapping studies from our laboratory suggest a direct role for insulin. Transgenic promoter reporter mice (Kim et al 2002, Kim et al 2007) were injected with insulin and hypothalamic luciferase levels measured by luminometer (Kim et al 2002, Wolfe et al 2002). This study was analogous to promoter mapping performed to identify a kisspeptin response element in the mouse GnRH promoter (Novaira et al 2012).…”
Section: Insulin Regulation Of Neuroendocrine Functionmentioning
confidence: 99%
“…Previous research defined a proximal promoter (21,43,48) and distal enhancer regions (42,48,55,65,82) that are critical for mammalian GnRH1 gene regulation. The proximal promoter is important for basal GnRH1 gene expression, and the distal enhancer region contains an enhancer sufficient for GnRH1 neuron-specific expression.…”
Section: Discussionmentioning
confidence: 99%
“…6). Multiple putative Pur protein binding sites are found in both the proximal promoter region and the distal enhancer region in mouse GnRH1 gene (48,56,65). Two GGGAGA sites are located in complementary strands in the distal enhancer region (Ϫ1,600 to Ϫ1,100 bp) of the A. burtoni GnRH1 gene.…”
Section: In Vivo Binding Of Pur Proteins To the Upstream Region Of Thmentioning
confidence: 99%